Mechanisms of subgrain coarsening and its effect on the mechanical properties of carbon-supersaturated nanocrystalline hypereutectoid steel. (1st February 2015) - Li, Y.J.; Kostka, A.; Choi, P.; Goto, S.; Ponge, D.; Kirchheim, R.; Raabe, D.
Abstract: Carbon-supersaturated nanocrystalline hypereutectoid steels with a tensile strength of 6.35 GPa were produced from severely cold-drawn pearlite. The nanocrystalline material undergoes softening upon annealing at temperatures between 200 and 450 ° C. The ductility in terms of elongation to failure exhibits a non-monotonic dependence on temperature. Here, the microstructural mechanisms responsible for changes in the mechanical properties were studied using transmission electron microscopy (TEM), TEM-based automated scanning nanobeam diffraction and atom probe tomography (APT). TEM and APT investigations of the nanocrystalline hypereutectoid steel show subgrain coarsening upon annealing, which leads to strength reduction following a Hall–Petch law. APT analyzes of the Mn distribution near subgrain boundaries and in the cementite give strong evidence of capillary-driven subgrain coarsening occurring through subgrain boundary migration. The pronounced deterioration of ductility after annealing at temperatures above 350 ° C is attributed to the formation of cementite at subgrain boundaries. The overall segregation of carbon atoms at ferrite subgrain boundaries gives the nanocrystalline material excellent thermal stability upon annealing.